Radiographic and clinical outcomes of robot-assisted pedicle screw instrumentation for adolescent idiopathic scoliosis - Chen, Yuan-Shao; Lin, Yu-Hsien; Wu, Yun-Che; Shih, Cheng-Min; Chen, Kun-Huei; Lee, Cheng-Hung; Lu, Wen-Hsien; Pan, Chien-Chou (Frontiers in Surgery, 2024)
Introduction Pedicle screw instrumentation (PSI) serves as the widely accepted surgical treatment for adolescent idiopathic scoliosis (AIS). The accuracy of screw positioning has remarkably improved with robotic assistance. Nonetheless, its impact on radiographic and clinical outcomes remains unexplored. This study aimed to investigate the radiographic and clinical outcomes of robot-assisted PSI vs. conventional freehand method in AIS patients. Methods Data of AIS patients who underwent PSI with all pedicle screws between April 2013 and March 2022 were included and retrospectively analyzed; those with hybrid implants were excluded. Recruited individuals were divided into the Robot-assisted or Freehand group according to the technique used. Radiographic parameters and clinical outcome measures were documented. Results In total, 50 patients (19, Freehand group; 31, Robot-assisted group) were eligible, with an average age and follow-up period of 17.6 years and 60.2 months, respectively, and female predominance (40/50, 80.0%). The correction rates of Cobb's angles for both groups were significant postoperatively. Compared to freehand, the robot-assisted technique achieved a significantly reduced breech rate and provided better trunk shift and radiographic shoulder height correction with preserved lumbar lordosis, resulting in significantly improved visual analog scale scores for back pain from the third postoperative month. Conclusion Overall, robot-assisted PSI provides satisfactory radiographic and clinical outcomes in AIS patients.